Evaluation of the sustainable development level of grain family farms in main grain-producing areas based on agricultural multi-function: a case study of Hunan Province in China - Duan, Wei; Pan, Yuehong (Frontiers in Sustainable Food Systems, 2024)
Introduction Grain family farms play an important role in promoting agricultural modernization and rural revitalization in China. Taking Hunan Province as an example, based on survey data from 400 grain family farms and agricultural multi-function theory, 24 specific indicators were selected from three dimensions-economic benefits, social benefits, and ecological benefits-to construct an evaluation system for the sustainable development level of grain family farms. Methods The entropy weight TOPSIS method was used to measure the sustainable development level of grain family farms in Hunan Province, and the obstacle factor diagnosis model was used to explore the main obstacle factors affecting the sustainable development of grain family farms. Results (1) The sustainable development level of grain family farms in Hunan Province was classified as good overall with respect to the classification criteria of existing relevant studies, but there were comparative differences in each dimension among the four regions (central Hunan, northern Hunan, southern Hunan, and western Hunan) of Hunan Province. (2) According to the diagnosis and analysis results of the obstacle degree, the top six obstacle factors affecting the sustainable development level of grain family farms in Hunan Province were the effective use of water resources, soil protection, and improvement efforts, the number of agricultural ecological culture inheritance activities, carbon emission management, the number of jobs provided for farmers, and adaptability to external environmental changes. Discussion Relevant policies and systems should be formulated based on local conditions to enhance the integrity and synergy of the development of grain family farms in Hunan Province and to enhance the sustainable development ability of grain family farms in Hunan Province.